Assessment of Factors that Contribute of Lung Cancer - Al-Ebrahimy, hussein (Iraqi National Journal of Nursing Specialties, 2005)
Abstract A descriptive study to assess of factors that contributes of lung cancer. The study was carried out in Specialized Surgery teaching hospital, Ibin Al- Beetar hospital and Ibin Al- Nafees hospital for the period From January 2004 to October 2004 .The study aimed to assess the factors that contribute to lung cancer and to identify the relationship between the variables of the study with lung cancer. A purposive (non-probability) sample of (70) patients with lung cancer was selected for the study. An assessment form was employed for the purpose of the study. Test- retest reliability was employed through computation of Pearson correlation coefficient. Content validity of the assessment was determined through a panel of experts. Data were collected through the interview technique. Data were analyzed through descriptive statistical approach (frequency and percentage) and inferential statistical approach (chi –square). The study showed that the majority of the study sample were (60-69) years old and most of them were male (65.7%) .The level of education was primary graduate (32.9%) and most of them were working in governmental officer. The result of the study showed that smoking is the majors’ factors that contribute to lung cancer. The study recommended stopping smoking, established special center to lung cancer in Iraq, regular chest exam to workers in the industry and need specialist nurse in cancer in Iraq.